Das Epos im Blick Intertextualität und Rollenkonstruktionen in Martials Epigrammen und Statius' Silvae - Baumann, Helge (Millennium-Studien / Millennium Studies, 2018)
In detailed case studies, Helge Baumann analyzes how Martial and Statius presented, integrated, and functionalized the epic into small poetic formats. These authors associated different situations, cultural practices, and actors with the epic. In the literary communication between poet and patron, the small format became an effective medium of role construction for authors and for their audiences.